The Effect of Learning Motivation and Science Learning Outcomes of Grade VIII Students at SMP Unismuh Makassar - Yusri Handayani (Jurnal Pendidikan Fisika, 2019)
Motivation is something that comes from within an individual that can influence individual activities to achieve goals in his life. Learning motivation influences learning objectives and impacts on learning outcomes. This journal aims to find out whether learning motivation influences students' natural science learning outcomes in Makassar Unismuh Middle School. The number of students in this study was 50 people. Data retrieval is done through learning motivation questionnaires and science learning outcomes tests. This study uses SPSS 24 to calculate the relationship or correlation between motivation and learning outcomes. This study resulted in a very significant relationship between motivation to learn and learning outcomes.Keywords: Learning Motivation, Learning OutcomesMotivasi adalah sesuatu yang berasal dari dalam diri individu yang dapat mempengaruhi kegiatan individu guna mencapai tujuan dalam hidupnya. Motivasi belajar mempengaruhi tujuan pembelajaran dan berdampak pada hasil belajar. Jurnal ini bertujuan untuk mengetahui apakah motivasi belajar berpengaruh terhadap hasil belajar IPA peserta didik di SMP Unismuh Makassar. Jumlah peserta didik dalam penelitian ini adalah 50 orang. Pengambilan data dilakukan melaui kuesioner motivasi belajar dan tes hasil belajar IPA. Penelitian ini menggunakan SPSS 24 untuk menghitung hubungan atau korelasi antara motivasi dan hasil belajar. Penelitian ini menghasilkan adanya hubungan yang sangat signifikan antara motivasi belajar dan hasil belajar.Kata kunci: Motivasi Belajar, Hasil Belajar